IMPLEMENTASI PROGRAM PENYANDANG MASALAH KESEJAHTERAAN SOSIAL (PMKS) DI KECAMATAN SUNGAI APIT TAHUN 2011 - Eko Purwanto; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Siak District Government through the Department of Social Welfare and Labor began to run a program created by the central government to improve the social welfare of society. The purpose of the program with social welfare problems is to improve people's quality of life and social welfare to all the poor and not able to achieve an optimal degree of public life effectively and efficiently. One of the goals of this program is the Community or poor families. Implementation Program with social welfare problems in Sungai Apit in 2011, it can be concluded that the poor implementation of the program problems had not been effective. This is due to the lack of qualified resources, will run effectively and efficiently if it is supported by a qualified staff and have qualified skills, good running information between the relevant parties can create management were also good, and the authority of the executing agency will be able to help Implementation of program implementation with social welfare problems in Sungai Apit Key word: Implementatio, Program, Disability, Social Welfare Issues